Incidence and timing of potentially high-risk arrhythmias detected through long term continuous ambulatory electrocardiographic monitoring. Issue 1 (December 2016) - Solomon, Matthew; Yang, Jingrong; Sung, Sue; Livingston, Martha; Sarlas, George; Lenane, Judith; Go, Alan
Abstract Background Ambulatory electrocardiographic (ECG) monitoring is the standard to screen for high-risk arrhythmias. We evaluated the clinical utility of a novel, leadless electrode, single-patient-use ECG monitor that stores up to 14 days of a continuous recording to measure the burden and timing of potentially high-risk arrhythmias. Methods We examined data from 122, 815 long term continuous ambulatory monitors (iRhythm ZIO® Service, San Francisco) prescribed from 2011 to 2013 and categorized potentially high-risk arrhythmias into two types: (1) ventricular arrhythmias including non-sustained and sustained ventricular tachycardia and (2) bradyarrhythmias including sinus pauses >3 s, atrial fibrillation pauses >5 s, and high-grade heart block (Mobitz Type II or third-degree heart block). Results Of 122, 815 ZIO® recordings, median wear time was 9.9 (IQR 6.8–13.8) days and median analyzable time was 9.1 (IQR 6.4–13.1) days. There were 22, 443 (18.3 %) with at least one episode of non-sustained ventricular tachycardia (NSVT), 238 (0.2 %) with sustained VT, 1766 (1.4 %) with a sinus pause >3 s (SP), 520 (0.4 %) with a pause during atrial fibrillation >5 s (AFP), and 1486 (1.2 %) with high-grade heart block (HGHB). Median time to first arrhythmia was 74 h (IQR 26–149 h) for NSVT, 22 h (IQR 5–73 h) for sustained VT, 22 h (IQR 7–64 h) for SP, 31 h (IQR 11–82 h) for AFP, and 40 h (SD 10–118 h) for HGHB. Conclusions A significant percentage of potentially high-risk arrhythmias are not identified within 48-h of ambulatory ECG monitoring. Longer-term continuous ambulatory ECG monitoring provides incremental detection of these potentially clinically relevant arrhythmic events.